Evaluation of block cipher “Cypress” strength against differential cryptanalysis - Rodinko, M.Yu. (Radiotekhnika, 2018)
This paper presents an evaluation of the practical strength of the lightweight block cipher “Cypress” to the differential cryptanalysis, which is determined by the probability of the best found differential characteristic. The paper proposes a mathematical model for evaluating the block cipher “Cypress” to differential cryptanalysis and methods for searching for multi-round differential characteristics. The first method is based on the combination of highly probable one-round differential characteristics into multi-round ones, while the second method is based on the extension of one-round characteristics for several rounds. As a result of the application of the second search method to the block cipher Cypress-256, a 6-round differential characteristic was found. Since it was not found a differential characteristics for more than six rounds with a probability which is higher than the probability of a brute-force attack, the block cipher Cypress-256 is practically resistant to differential cryptanalysis.